ANALISIS PENGARUH FINANCIAL STRENGTH, RISIKO BISNIS, INVESTEMENT OPPORTUNITY, STRUCTURE ASSETS, DAN RETURN ON ASSETS TERHADAP FINANCIAL LEVERAGE (Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2011-2013) - Ria Ariyanti, 11.05.52.0084; Suwarti, Titiek (Students Journal of Accounting and Banking, 2015)
This study was conducted to examine the effect of financial strength, business risk, opportunity Investments, asset structure and return on assets to financial leverage. The population used in this research are manufacturing companies listed in Indonesia Stock Exchange during 2011-2013.The sampling technique used is pusposive sampling. The number of samples obtained as much as 68 manufacturing companies. The analysis technique used is multiple linear regression analysis and using t-test, Model test with significance level Î± = 5%. It also made the classic assumption test including normality test, multicolinearity test, test and test heteroskedastisitas autokorelasi. Results of the analysis can be concluded that the financial strength, business risk and asset structure and significant positive effect on financial leverage. While the investment opportunity has no influence on financial leverage. And proceeds to ROA significant negative effect on financial leverage. For further research is recommended to investigate all companies listed on the Stock Exchange, not only manufacturing companies alone so that it can be generalized to all companies.Keywords: Financial Strength, Business Risk, Opportunity Investments, Asset Structure, Return On Assets, Financial Leverage